Complete Genome Sequence of Mesorhizobium ciceri bv. biserrulae Strain WSM1284, an Efficient Nitrogen-Fixing Microsymbiont of the Pasture Legume Biserrula pelecinus. - Haskett, T.; Wang, P.; Ramsay, Joshua; O'Hara, G.; Reeve, W.; Howieson, J.; Terpolilli, J. (American Society for Microbiology, 2016)
We report the complete genome sequence of Mesorhizobium ciceri bv. biserrulae strain WSM1284, a nitrogen-fixing microsymbiont of the pasture legume Biserrula pelecinus The genome consists of 6.88 Mb distributed between a single chromosome (6.33 Mb) and a single plasmid (0.55 Mb).